2021
DOI: 10.2147/opth.s272345
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations of Cuticular Drusen: Current Perspectives

Abstract: Cuticular drusen are part of the spectrum of age-related macular degeneration (AMD) with particular clinical and multimodal imaging characteristics. This drusen subpopulation shares several high-risk single nucleotide polymorphisms with AMD. Despite this feature, they can manifest at a relatively young age, presenting with a female preponderance. Multimodal imaging is essential for characterizing such lesions, using a combination of color fundus photographs, optical coherence tomography (OCT), fluorescein angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…We confirmed the presence of cuticular drusen in 10 eyes (62.5%), while others noted a prevalence of AVLs in patients with cuticular drusen from 1.2% to 24.2% [20]. The same author observed that the association between the AVL and cuticular drusen seems to lead to a collapse with the resolution of the vitelliform material, doubled by RPE failure and atrophy with the disappearance of drusen [20]. Contrary to another study in which all the 32 eyes belonging to 24 patients presented serous PED [21], we found only 2 eyes (12.5%) with RPE detachment.…”
Section: Discussionsupporting
confidence: 82%
“…We confirmed the presence of cuticular drusen in 10 eyes (62.5%), while others noted a prevalence of AVLs in patients with cuticular drusen from 1.2% to 24.2% [20]. The same author observed that the association between the AVL and cuticular drusen seems to lead to a collapse with the resolution of the vitelliform material, doubled by RPE failure and atrophy with the disappearance of drusen [20]. Contrary to another study in which all the 32 eyes belonging to 24 patients presented serous PED [21], we found only 2 eyes (12.5%) with RPE detachment.…”
Section: Discussionsupporting
confidence: 82%
“…However, drusen may also occur at younger ages, often forming recognizable patterns suggestive of an inherited disease, such as the dominantly inherited drusen phenotypes of Malattia leventinese and Doyne’s honeycomb dystrophy rather than typical age-related deposits [ 24 ]. Cuticular drusen are another drusen subtype of round yellow lesions between 50 and 75 µm in diameter that can appear at a relatively young age [ 25 , 26 ]. In time, genetic analysis may be able to differentiate individuals with different drusen phenotypes from those with typical AMD drusen and may help to uncover their unique etiology; these subtypes may require a different treatment strategy to the more typical conventional drusen phenotypes.…”
Section: Structural Biomarkersmentioning
confidence: 99%
“…The diffuse involvement and/or accompanying large drusen in patients older than 60 years may confer a significant risk of either MNV or GA in White ethnic groups; macular complications of cuticular drusen were comparable with those of soft drusen in this age group [ 66 , 67 ]. The life cycles of cuticular drusen phenotypes were defined in a large cohort of White patients using multimodal imaging in a retrospective, observational cohort study involving 240 eyes of 120 clinic patients with a cuticular drusen phenotype in a White ethnic group, with a mean age of patients at the first visit of 57.9 ± 13.4 years.…”
Section: Stratifying the Risk Of Advanced Amd: Emerging Drusen Subtyp...mentioning
confidence: 99%